The Effect of Dividend Policy and Market Ratio on Stock Returns of Blue Chip Companies Listed on the Indonesia Stock - Syaiful Anwar Zainuddin; Dudi Rudianto (Jurnal Multidisiplin Sahombu, 2025)
This study aims to analyze the effect of dividend policy and market ratio on stock returns of blue chip companies listed on the Indonesia Stock Exchange (IDX) during the 2018–2024 period. The market ratio is proxied by Price to Book Value (PBV), while dividend policy is proxied by Dividend Yield (DY) and Dividend Payout Ratio (DPR). The research method employed is quantitative with a causal approach. The sample consists of 14 blue chip companies with large market capitalization and high liquidity. Secondary data were obtained from the IDX, financial statements, and other financial publications, and were analyzed using multiple linear regression with the assistance of SPSS version 25. The results show that Price to Book Value (PBV) has no significant effect on blue chip stock returns, while Dividend Yield (DY) has a positive and significant effect and Dividend Payout Ratio (DPR) has a negative and significant effect on stock returns. However, simultaneously, the three variables significantly affect stock returns. These findings indicate that investors tend to value higher dividend yields but remain cautiously toward companies that distribute excessively large payouts as it may compromise long-term growth potential. Meanwhile, book-value-based valuation (PBV) does not serve as a primary consideration for investors in the short term, especially under market conditions influenced by external factors such as global economic uncertainty.